Analysis of Green Inclusive Development Achievements at the Provincial Level in Indonesia; Balanced Inclusive Green Growth Index Method - Diartho, Herman Cahyo; Pratama, Alif Fani Egi; Kangkha, Patcharin (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
The Balanced Inclusive Green Growth Index (BIGGI) offers a comprehensive framework for evaluating sustainable development by integrating economic, social, and environmental dimensions. This study aims to assess the application of BIGGI across Java Island, Indonesia, a key region contributing significantly to the nation’s GDP and Sustainable Development Goals (SDGs). Using cross-sectional data from 2023 and factor analysis, the research identifies disparities among 107 districts and cities. Results reveal that 68 regions achieved high BIGGI scores (>1.000), reflecting a balance in green growth dimensions, while 13 regions scored ≤0.500 due to economic stagnation despite strong social indices. The methodology includes data normalization using the Min-Max approach and factor analysis validated through the Bartlett and Kaiser-Meyer-Olkin (KMO) tests. These techniques consolidate multiple variables into a single composite index. Findings emphasize the need for targeted local government interventions, particularly in low-performing regions, to address economic disparities through infrastructure development, renewable energy investments, and policy enhancements. This research contributes to sustainable development literature by providing actionable insights for policymakers to implement equitable and inclusive green growth strategies. The study underscores the utility of BIGGI as a replicable framework for regions with similar socio-economic and environmental challenges, aligning local development efforts with global SDGs.